‘Copy and paste’ in undergraduate research: abusing Internet - Huamaní, Charles (2013)
Objectives: ethics in the research process is an issue little discussed during the undergraduate and therefore should be analyzed to prevent breaches that could affect the development of the researcher in training. Design: Retrospective observational study. Lugar: Facultad de Medicina, Universidad Nacional Mayor de San Marcos. Population: Section of the ‘introduction’ of research works conducted in 2004 in a course curriculum. Interventions: Manually reviewed the prayers of the ‘introduction’ of works, describes the type of copy, the number of works, authors, consultants, copied paragraphs, and the type of information sources and copying. Principal outcome measures: frequencies and percentages of prayers copied and type of copy. Results: It reviewed a total of 24 research papers, with an average of 6 authors and 2 advisers for work, 23 had some evidence of electronic copy, only 8 were literal copies; of the total prayers reviewed, 64% corresponds to complete copy of prayers; only 30% of the sources were copied scientific publications online, other sources were copied publicly available non-specialists. Conclusions: describes a high frequency of copy during the undergraduate research from electronic sources, so it is necessary to prevent its recurrence in future research and implement systems systematic search for plagiarism.